Emulgel formulation of wild cherry leaves (Antidesma bunius L. Spreng) extract and its antioxidant activity - Windah Anugrah Subaidah; Yayuk Andayani; Dewa Ayu Puspaning Kumaradewi (Acta Pharmaciae Indonesia : Acta Pharm Indo, 2022)
Background: The ethanol extract of wild cherry leaves (Antidesma bunius L. Spreng) has been studied as a free anti-radical in an emulgel formulation. The purpose of this study is to determine the physical properties of an emulgel made from an ethanol extract of wild cherry leaves, as well as its anti-radical activity. Methods: The maceration method was used to extract wild cherry leaves in 96% ethanol, which were then evaporated with a rotary evaporator. An emulgel was prepared to contain a 3.56% thick extract. The physical properties of the emulgel were evaluated consisting of the organoleptic test, pH test, homogeneity test, spreadability test, and adhesion test. The DPPH was used to test free anti-radical activity. Results: The emulgel of the ethanol extract of wild cherry leaves had a yellowish-green, thick texture, a distinct aroma of the extract, was homogeneous, pH 6, spreadability ranged from 4.4-6.2 cm, and adhesion of 5.467 0.83 cm. Emulgel had a very weak antioxidant activity with an IC50 of 6238.41 ppm. Conclusion: